Linguistic Constructive Approach in Science Class - Doss, Prasannakumar (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
The present study examines the effectiveness of Linguistic constructive approach in enhancing achievement in Science among V Standard students. An experimental design has been adopted. Linguistic constructive approach is independent variable and achievement in science is the dependent variable. Thirty students of standard 5th of a local School here the sample of subjects. The data of achievement in science on pre and post assessment were collected and computed for analysis. From statistical findings it is concluded that the Linguistic constructive approach enhancing the achievement in science of the students.